2020 International Consensus on First Aid Science With Treatment Recommendations. Issue 16 (20th October 2020) - Singletary, Eunice M.; Zideman, David A.; Bendall, Jason C.; Berry, David C.; Borra, Vere; Carlson, Jestin N.; Cassan, Pascal; Chang, Wei-Tien; Charlton, Nathan P.; Djärv, Therese; Douma, Matthew J.; Epstein, Jonathan L.; et al.
Abstract : This is the summary publication of the International Liaison Committee on Resuscitation's 2020 International Consensus on First Aid Science With Treatment Recommendations . It addresses the most recent published evidence reviewed by the First Aid Task Force science experts. This summary addresses the topics of first aid methods of glucose administration for hypoglycemia; techniques for cooling of exertional hyperthermia and heatstroke; recognition of acute stroke; the use of supplementary oxygen in acute stroke; early or first aid use of aspirin for chest pain; control of life-threatening bleeding through the use of tourniquets, hemostatic dressings, direct pressure, or pressure devices; the use of a compression wrap for closed extremity joint injuries; and temporary storage of an avulsed tooth. Additional summaries of scoping reviews are presented for the use of a recovery position, recognition of a concussion, and 6 other first aid topics. The First Aid Task Force has assessed, discussed, and debated the certainty of evidence on the basis of Grading of Recommendations, Assessment, Development, and Evaluation criteria and present their consensus treatment recommendations with evidence-to-decision highlights and identified priority knowledge gaps for future research. Abstract : Supplemental Digital Content is available in the text.